Chronicles of a primary care practice pharmacist - Freeman CR; Cottrell WN; Kyle G; Williams ID; Nissen LM (Dove Medical Press, 2012)
Christopher R Freeman,1 W Neil Cottrell,1 Greg Kyle,2 Ian D Williams,3 Lisa M Nissen11School of Pharmacy, University of Queensland, Brisbane, Australia; 2Faculty of Health, University of Canberra, Canberra, Australia; 3Camp Hill Healthcare, Camp Hill, Brisbane, AustraliaBackground: In 2009, a pharmacist commenced working in a nondispensing role at a primary care medical center located in a metropolitan suburb of Brisbane, Australia. Research into the role and function of a practice pharmacist in this setting is still in its infancy.Methods: Ethnographic methods were used over a 3-month period to record activities undertaken by the practice pharmacist on a daily basis.Results: During the 3-month period, 296 hours of activity were documented. Activities the practice pharmacist performed most frequently included medication review, “pharmaceutical opinion,” student supervision, drug information, and administrative tasks.Conclusion: This study demonstrates the broad range of activities which were conducted by a practice pharmacist in the primary care setting as part of a multidisciplinary team.Keywords: practice pharmacist, general practice, integration, medical center